Motion-compensated prediction based algorithm for medical image sequence compression - OGUZ, S. H; GEREK, O. N; CETIN, A. E (Signal processing. Image communication, 1995)
A method for irreversible compression of medical image sequences is described. The method relies on discrete cosine transform and motion-compensated prediction to reduce intra- and inter-frame redundancies in medical image sequences. Simulation examples are presented.